2007
DOI: 10.1068/p5637
|View full text |Cite
|
Sign up to set email alerts
|

Things are Looking up: Differential Decline in Face Recognition following Pitch and Yaw Rotation

Abstract: Previous research into the effects of viewpoint change on face recognition has typically dealt with rotations around the head's vertical axis (yaw). Another common, although less studied, source of viewpoint variation in faces is rotation around the head's horizontal pitch axis (pitch). In the current study we used both a sequential matching task and an old/new recognition task to examine the effect of viewpoint change following rotation about both pitch and yaw axes on human face recognition. The results of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 36 publications
5
31
0
Order By: Relevance
“…Overall, the authors found that people were much faster at recognizing their own face than their colleagues’ faces, but recognition of colleagues’ faces was much more tolerant of a viewpoint change. Similarly, researchers have reported better performance recognizing faces across in-depth rotations compared to pitch rotations, looking up or looking down, and performance was better for pitch rotations of an upward compared to downward rotation (Favelle et al 2007). This also supports the finding that face recognition is highly dependent on one’s experience with different viewpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the authors found that people were much faster at recognizing their own face than their colleagues’ faces, but recognition of colleagues’ faces was much more tolerant of a viewpoint change. Similarly, researchers have reported better performance recognizing faces across in-depth rotations compared to pitch rotations, looking up or looking down, and performance was better for pitch rotations of an upward compared to downward rotation (Favelle et al 2007). This also supports the finding that face recognition is highly dependent on one’s experience with different viewpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Viewpoint effects on face recognition have predominantly been examined by using yaw rotations (about the vertical axis) and roll rotations (about the picture plane). Only recently have studies started to examine viewpoint effects for faces following pitch rotation (about the horizontal axis) (Favelle et al 2007;Liu et al 2005;Wallraven et al 2002). This research has shown that there are marked differences in recognition performance following rotations about the pitch and yaw axes.…”
Section: Introductionmentioning
confidence: 99%
“…(1) The labeling of the pitch-up and pitch-down conditions in Favelle et al (2007) mistakenly refers to head rotation and not viewpoint rotation, ie the opposite of the current paper. The pitch-rotated face stimuli are identical in these two papers.…”
Section: Introductionmentioning
confidence: 99%
“…In Experiment 1 we vary the views available, a manipulation well-known to affect sensitivity (Bruce et al, 1987; Hill et al, 1997; Troje and Bulthoff, 1998; Favelle et al, 2007), especially for unfamiliar faces (Hancock et al, 2000). In many of the studies cited above the faces being compared were presented in the same view (Freire et al, 2000; Mondloch et al, 2002; Rhodes et al, 2007; Dakin and Omigie, 2009; Ross et al, 2010) and this allows decisions to be based on image differences alone: all differences in the images presented result from differences between the faces.…”
Section: Introductionmentioning
confidence: 99%